Identification of chloroplast genome loci suitable for high‐resolution phylogeographic studies of Colocasia esculenta (L.) Schott (Araceae) and closely related taxa. (30th May 2013) - Ahmed, Ibrar; Matthews, Peter J.; Biggs, Patrick J.; Naeem, Muhammad; McLenachan, Patricia A.; Lockhart, Peter J.
Abstract Recently, we reported the chloroplast genome‐wide association of oligonucleotide repeats, indels and nucleotide substitutions in aroid chloroplast genomes. We hypothesized that the distribution of oligonucleotide repeat sequences in a single representative genome can be used to identify mutational hotspots and loci suitable for population genetic, phylogenetic and phylogeographic studies. Using information on the location of oligonucleotide repeats in the chloroplast genome of taro (Colocasia esculenta), we designed 30 primer pairs to amplify and sequence polymorphic loci. The primers have been tested in a range of intra‐specific to intergeneric comparisons, including ten taro samples (Colocasia esculenta) from diverse geographical locations, four other Colocasia species (C. affinis, C. fallax, C. formosana, C. gigantea) and three other aroid genera (represented by Remusatia vivipara, Alocasia brisbanensis and Amorphophallus konjac). Multiple sequence alignments for the intra‐specific comparison revealed nucleotide substitutions (point mutations) at all 30 loci and microsatellite polymorphisms at 14 loci. The primer pairs reported here reveal levels of genetic variation suitable for high‐resolution phylogeographic and evolutionary studies of taro and other closely related aroids. Our results confirm that information on repeat distribution can be used to identify loci suitable for such studies, and we expect that this approach can be used in other plant groups.